1994
DOI: 10.2172/10190378
|View full text |Cite
|
Sign up to set email alerts
|

Flammable gas safety program. Analytical methods development: FY 1994 progress report

Abstract: This report was .prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, make any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…The organic components of the convective layer will be analyzed under the Actual Waste Organic Analysis task according to procedures outlined in Campbell et al 1994. The organic analysis is still under way; these data will be reported in a subsequent report that will also include the gamma enhanced gas generation data.…”
Section: Experimental Conditions and Equipmentmentioning
confidence: 99%
“…The organic components of the convective layer will be analyzed under the Actual Waste Organic Analysis task according to procedures outlined in Campbell et al 1994. The organic analysis is still under way; these data will be reported in a subsequent report that will also include the gamma enhanced gas generation data.…”
Section: Experimental Conditions and Equipmentmentioning
confidence: 99%
“…Early work (Delegard 1980(Delegard , 1987 implied that new organic compounds derived from the original organic substances were being formed and were accumulating in the waste tanks. This suggestion was confirmed by subsequent work that demonstrated the presence of new substances such as iminodiacetate ion (IDA) -NH(CH2COY)z -and oxidized compounds such as formate ion, neither of which had been employed in waste processing operations (Campbell et al 1994). These results strongly suggested that the organic constituents were being oxidized under the influence of the radiation field.…”
Section: Evidence For Organic Compound Oxidation From Characterizatiomentioning
confidence: 67%
“…The organic compounds in the wastes have been identified by gas and liquid chromatography, mass spectrometry, and other advanced analytical methods (Campbell et al 1994Pool and Bean 1994;Wahl et al 1995). The concentrations of the original complexants and their principal oxidation products have been determined in the laboratories at the Hanford Site and the Pacific Northwest National Laboratory for samples from more than 20 single-shell and double-shell tanks (Campbell et al 1994Pool and Bean 1994;Wahl et al 1995).…”
Section: Organic Complexant Species In Solid and Liquid Samples From mentioning
confidence: 99%
See 2 more Smart Citations